2012
DOI: 10.2165/11595270-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Dimensional View of Access to Licensed and Subsidized Medicines under Single-Payer Systems in the US, the UK, Australia and New Zealand

Abstract: The single-payer systems examined differ in the number and age of licensed and subsidized entities, along with access to innovative entities. The NHS subsidized the most entities, the newest entities and the most innovative entities. NZ's PHARMAC system subsidized the fewest and oldest entities, and the fewest innovative entities. The VANF and PBS consistently fell between the other two systems in terms of the number of subsidized entities, age of subsidized entities and number of subsidized innovative entitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Yet, it is this very combination residing in Pharmac that has engendered the most criticism and industry concern. Pharmac's utilitarian approach of providing the greatest good for the greatest number within its budget has worked well, with the caveat that some New Zealanders miss out on or have delayed access to medicines available in other countries [1,22]. The agency has also emerged as something of an international role model for evidence-informed decision making.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, it is this very combination residing in Pharmac that has engendered the most criticism and industry concern. Pharmac's utilitarian approach of providing the greatest good for the greatest number within its budget has worked well, with the caveat that some New Zealanders miss out on or have delayed access to medicines available in other countries [1,22]. The agency has also emerged as something of an international role model for evidence-informed decision making.…”
Section: Resultsmentioning
confidence: 99%
“…First, studies variously suggest that New Zealanders have access to a more limited range of medicines, which are older and less innovative, than comparator health systems meaning patients with specific diseases often wait longer for access knowing that medicines are publicly subsidised in other countries [1,22]. The implication is that Pharmac is to blame.…”
Section: Pharmac's Performancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ragupathy et al (2012) compared lists of licensed and subsidised medicines to compare aspects of access to medicines in different countries. Many studies have examined the quantity and quality of information presented in medicines advertisements (Rohra et al 2006).…”
Section: Analysis Of Other Documents Related To Medicinesmentioning
confidence: 99%
“…[10,[13][14][15] A study comparing medicines funded in NZ in 2007 with that of Finland, found that fewer medical entities were funded in NZ than in Finland's public health system (471 versus 495), [16] and a similar study found that NZ funded fewer entities than the USA, UK and Australia in the same year. [17] Other comparisons have been made, especially with neighbouring Australia's Pharmaceutical Benefits Scheme, finding a slower uptake of new medicines by PHARMAC on behalf of NZ [18] ; however, the interpretation of such findings should be considered alongside the fact that PHARMAC explicitly requires proof of added benefit before funding a medicine. [19] Slower funding, or lack of funding, for sub-types of medicines, such as high cost and highly specialised medicines, has also been criticised by NZ researchers [20,21] and there are reports that some NZ patients have emigrated to Australia in order to access necessary treatment for multiple sclerosis and HIV infection.…”
Section: Introductionmentioning
confidence: 99%